Ethics as an enabler and a constraint – Narratives on technology development and artificial intelligence in military affairs through the case of Project Maven - Malmio, Irja (Technology in society, 2023)
Project Maven is an AI-induced information technology for military applications initiated by the United States Department of Defence (DoD) in 2017 and originally signed on to a civilian contractor, namely Google. However, this initiative raised massive resistance from a substantial amount of Google employees, eventually leading to the contract's annulation. This article uses narrative analysis to investigate enabling and constraining arguments of AI for military purposes that appeared in the debate following the public announcement of Project Maven. In addition, the article highlights the co-production of ethics, technology, and the complex issues that arise from civilian-military exchanges in technology development. Enabling arguments associated with consequentialist ethics are identified as narratives of accuracy and maintenance. Accuracy constitutes a guiding principle for saving civilian lives, while maintenance is directed at keeping the power balance intact. In contrast, constraining arguments proceed from deontological ethics that emphasize disengagement and ambivalence. Disengagement amplifies a civilian/military divide, while ambivalence exhibits conflicting views concerning the prospect of supplementing technological solutions that have the potential to contribute to war and civilian casualties. Conclusively, security narratives and technological storytelling are important aspects to consider since they hold a performative function that influences the framing and mobilization of security and technology development. •Narratives on technology development and security are important building blocks when analyzingsecuritized technologies and social life.•Technologies are co-creators of societal norms , and are important factors for how society mediates its ethical standard.•The Narratives identified from the case of Project Maven illustrate how security and technology development are framed and mobilized.•Narratives on AI and Technology development contain constraining (deontological) and enabling (consequentialist) properties .